2021
DOI: 10.1177/23197145211021564
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Performance of Commercial Banks: A Dynamic Panel Study on India

Abstract: The article investigates the determinants of commercial banks’ performance in India over the period from 2000 to 2017 with special reference to the macroeconomic factors. Considering return on assets (ROA), return on equity (ROE) and net interest margin (NIM) as the measure of performance, we have chosen a panel of public and private sector commercial banks of our country. Taking some macro variables such as GDP, inflation and lending interest rate as the prime explanatory variables along with some bank-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…However, ref. [74] revealed that increasing unemployment causes a rise in banks' profitability in India.…”
Section: Sovereign Social Performancementioning
confidence: 99%
“…However, ref. [74] revealed that increasing unemployment causes a rise in banks' profitability in India.…”
Section: Sovereign Social Performancementioning
confidence: 99%
“…As macroeconomic variables, the inflation rate (IR) and the GDP growth rate (GDPGR) are measured and found to be positive and significant for ROA". Sarkar, S., & Rakshit, D. [54] investigated "the determinants of commercial banks' performance in India over the period from 2000 to 2017 with special reference to the macroeconomic factors. They were ted return on assets (ROA), return on equity (ROE) and net interest margin (NIM) as the measure of bank performance and also took some external variables such as GDP, inflation, and lending interest rate as the prime explanatory variables along with some bankspecific and macroeconomic control variables.…”
Section: Vasanimentioning
confidence: 99%
“…Finally, in terms of methodology, to enhance the robustness of the results, this study utilizes an advanced approach-the generalized method of moments (GMM). The GMM is a widely recognized econometric technique that offers several advantages, particularly in addressing endogeneity issues inherent in panel data analysis (Chowdhury et al 2017;Zarrouk et al 2016;Rahman et al 2020;Sarkar and Rakshit 2021). By employing the GMM, we can effectively mitigate potential biases arising from endogeneity, such as omitted variable bias and simultaneity, which could otherwise distort our estimation results.…”
Section: Introductionmentioning
confidence: 99%